Sustainable Ecotourism Communication Framework Based on Social and Cultural Capital to Build Community Engagement in Ecotourism Practices Rutong Tourism Village, Indonesia - ORATMANGUN, Dharma; WIDANINGSIH, Themotia Titi; MURTININGSIH, Bertha Sri Eko (Journal of Environmental Management and Tourism, 2025)
Rutong Tourism Village in Ambon has rich cultural and natural tourism potential, but its management is traditional and pays little attention to sustainable ecotourism. Sustainability communication practices, which leverage social and cultural capital, are essential to building community involvement in sustainable ecotourism in Rutong tourism village. This research will examine community and culture-based sustainable tourism communications to build involvement in sustainable ecotourism practices in Rutong village. The study uses qualitative methods to analyze community-based and culturally sustainable tourism communication in Rutong. The results of the study show that Rutong tourist village development is based on customary and traditional values, with community participation through social networks, trust and cooperation. Traditional values are guidelines in community life and tourism development, such as the Sasi traditional system of managing seas and forests implementation of Saniri for joint decision-making. Masohi's value is to build togetherness and cooperation. Tourist activities showcase Rutong cultural authenticity, starting from staying in a homestay, traditional welcoming, cultural attractions in dance, music, and games, traditional sago processing, and traditional food and drink preparations. Sustainability efforts are carried out through community-based waste management, environmental education, Integrating environmental education into the school curriculum, alternative energy development, plastic reduction campaigns, and tumbler use. Communication is carried out in an informative, transparent, and persuasive manner through dialogue, training, awards, and cooperation with NGOs and universities. This Communication is effective in creating community awareness and participation in sustainable tourism development.